Comparison of external and internal implant-abutment connections for implant supported prostheses. A systematic review and meta-analysis - Lemos, Cleidiel Aparecido Araujo [UNESP]; Verri, Fellippo Ramos [UNESP]; Bonfante, Estevam Augusto; Santiago Júnior, Joel Ferreira; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2018)
Objective: The systematic review and meta-analysis aimed to answer the PICO question: “Do patients that received external connection implants show similar marginal bone loss, implant survival and complication rates as internal connection implants?”. Data: Meta-analyses of marginal bone loss, survival rates of implants and complications rates were performed for the included studies. Study eligibility criteria included (1) randomized controlled trials (RCTs) and/or prospective, (2) studies with at least 10 patients, (3) direct comparison between connection types and (4) publications in English language. The Cochrane risk of bias tool was used to assess the quality and risk of bias in RCTs, while Newcastle-Ottawa scale was used for non-RCTs. Source: A comprehensive search strategy was designed to identify published studies on PubMed/MEDLINE, Scopus, and The Cochrane Library databases up to October 2017. Study selection: The search identified 661 references. Eleven studies (seven RCTs and four prospective studies) were included, with a total of 530 patients (mean age, 53.93 years), who had received a total of 1089 implants (461 external-connection and 628 internal-connection implants). The internal-connection implants exhibited lower marginal bone loss than external-connection implants (P < 0.00001; Mean Difference (MD): 0.44 mm; 95% Confidence interval (CI): 0.26–0.63 mm). No significant difference was observed in implant survival (P = 0.65; Risk Ratio (RR): 0.83; 95% CI: 0.38–1.84), and complication rates (P = 0.43; RR: 1.15; 95% CI: 0.81–1.65). Conclusion: Internal connections had lower marginal bone loss when compared to external connections. However, the implant-abutment connection had no influence on the implant's survival and complication rates. Based on the GRADE approach the evidence was classified as very low to moderate due to the study design, inconsistency, and publication bias. Thus, future research is highly encouraged. Clinical significance: Internal connection implants should be preferred over external connection implants, especially when different risk factors that may contribute to increased marginal bone loss are present.
Keywords: Bone loss; Complication; External connection; Implant survival; Internal connection; Systematic review